Robust Microporous Metal–Organic Frameworks for Highly Efficient and Simultaneous Removal of Propyne and Propadiene from Propylene. (24th June 2019) - Peng, Yun‐Lei; He, Chaohui; Pham, Tony; Wang, Ting; Li, Pengfei; Krishna, Rajamani; Forrest, Katherine A.; Hogan, Adam; Suepaul, Shanelle; Space, Brian; Fang, Ming; Chen, Yao; et al.
Abstract: Simultaneous removal of trace amounts of propyne and propadiene from propylene is an important but challenging industrial process. We report herein a class of microporous metal–organic frameworks (NKMOF‐1‐M ) with exceptional water stability and remarkably high uptakes for both propyne and propadiene at low pressures. NKMOF‐1‐M separated a ternary propyne/propadiene/propylene (0.5 : 0.5 : 99.0) mixture with the highest reported selectivity for the production of polymer‐grade propylene (99.996 %) at ambient temperature, as attributed to its strong binding affinity for propyne and propadiene over propylene. Moreover, we were able to visualize propyne and propadiene molecules in the single‐crystal structure of NKMOF‐1‐M through a convenient approach under ambient conditions, which helped to precisely understand the binding sites and affinity for propyne and propadiene. These results provide important guidance on using ultramicroporous MOFs as physisorbent materials. Abstract : Offene Bevorzugung : Eine Klasse mikroporöser wasserstabiler MOFs ermöglicht die gleichzeitige Entfernung von Propin‐ und Propadienspuren aus Propylen, das bei Umgebungstemperatur in Polymerqualität (99.996 %) gewonnen wird. Ein Verfahren zur Visualisierung der Propin‐ und Propadienmoleküle in der MOF‐Einkristallstruktur trug zur Klärung der starken Bindungsaffinität für Propin und Propadien gegenüber Propylen bei.